2020
DOI: 10.21608/edj.2020.31768.1136
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Fibrin Versus Hyaluronic Acid as palatal wound Dressings following epithelialized free gingival graft harvest: A randomized controlled clinical trial

Abstract: Introduction: Patient centered outcome became of great interest nowadays. Patient's pain and discomfort following free gingival graft procedure are common complain. Different palatal dressings are suggested to cover and protect the palatal donor site as stents, collagen gelatin scaffolds, platelet rich fibrin (PRF), hyaluronic acid (HA) and Alvogyl. However, in the literature no ideal agent has been emphasized. Objectives: This randomized controlled clinical trial compares for the first-time the effect of PRF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…(2022) observed that collagen hemostatic sponge promoted better pain control when associated with hyaluronic acid gel than with periodontal dressing. In comparison to L‐PRF, lower pain levels were obtained for L‐PRF in comparison to collagen hemostatic sponge in three studies (Femminella et al., 2016; Hassan et al., 2020; Sousa et al., 2020), however, collagen hemostatic sponge promoted more less levels of pain in comparison to L‐PRF in one case series (Belkhede et al., 2019). Schinini et al.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…(2022) observed that collagen hemostatic sponge promoted better pain control when associated with hyaluronic acid gel than with periodontal dressing. In comparison to L‐PRF, lower pain levels were obtained for L‐PRF in comparison to collagen hemostatic sponge in three studies (Femminella et al., 2016; Hassan et al., 2020; Sousa et al., 2020), however, collagen hemostatic sponge promoted more less levels of pain in comparison to L‐PRF in one case series (Belkhede et al., 2019). Schinini et al.…”
Section: Resultsmentioning
confidence: 97%
“…Lower pain scores (Bahammam, 2018; Femminella et al., 2016; Hassan et al., 2020; Işler et al., 2019; Kulkarni et al., 2014; Lektemur Alpan & Torumtay Cin, 2020; Ozcan et al., 2017; Shakir et al., 2015) and analgesic consumption (Bahammam, 2018; Femminella et al., 2016; Lektemur Alpan & Torumtay Cin, 2020) were reported in the palatal donor area covered with L‐PRF in comparison to spontaneous healing (Lektemur Alpan & Torumtay Cin, 2020; Shakir et al., 2015), non‐eugenol pack (Bahammam, 2018; Kulkarni et al., 2014), collagen hemostatic sponge (Femminella et al., 2016; Hassan et al., 2020), hyaluronic acid gel (Hassan et al., 2020), cyanoacrylate adhesive (Ozcan et al., 2017) and topical gaseous ozone (Işler et al., 2019). One case series (with three patients per group) showed superior results for collagen hemostatic sponge in comparison to L‐PRF in terms of pain duration and analgesic consumption (Belkhede et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations